Informasi Keanekaragaman Batik Pulau Jawa Berbasis Android - Budi Utami Fahnun; Bangkit Hardiansyah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Batik is an invaluable asset of the country Indonesia should therefore be preserved, besides batikshould be protected so as not to be recognized and taken other countries. To preserve batik in Indonesia,it requires good socialization to the entire community, especially the next generation of expensive art thatwas not lost or recognized other countries. Diversity Java Batik is a lot of information not known by thepublic so that sometimes people do not know if it is on the island of Java has a diverse batik. Of the aboveproblems, necessary applications to allow users to find the information diversity of batik, especially theisland of Java in a way that is easier to use android based mobile devices. In this paper discussed how tocreate applications using the Java programming language and XML ranging from drafting to display codingwriting programKeywords: Application Mobile, Android, Java, XML, Java Batik Diversity